From Azania to the new South Africa: Thinking with Neville Alexander - Painter, Desmond (PINS-Psychology in Society, 2025)
Alexander, Neville (2013) Thoughts on the New South Africa. Johannesburg: Jacana. ISBN 978-1431405862. 232 Pages. When Neville Alexander died in 2012 he was 75 years old. He could look back on a long and significant – and certainly exemplary – life as an activist, scholar and public intellectual. Yet it is difficult not to think of Neville Alexander as someone who had died too soon. More than just a role model for a younger generation of academics, committed intellectuals, and campaigners for a democratic socialist alternative in South Africa, Alexander was at the time of his death very much still a fellow traveller; a generous, durable and effervescent participant and partner in all manner of critical and reconstructive dialogues and projects. Completed shortly before his death and published posthumously, Thoughts on the New South Africa certainly reinforces the impression of a vital voice interrupted.